Church and education in the Central African Republic: the contribution of Enseignement Catholique Associé to the Nation - (:unkn) unknown (My University, 2006)
Research essay on the contribution of Catholic schools to the Central African education system. Master's Thesis in Educational Sciences.
Keywords: African Research